Pengaruh Penambahan Jenis Buah (Naga Merah (Hylocereus polyrhizus l.), Pisang Ambon (Musa paradisiaca), Stroberi (Fragaria ananassa)) dan Persentase Penambahannya Terhadap pH, Total Asam dan Viskositas Yogurt - Harnowo Sidhi; Siti Rahmawati Zulaikhah (UNU Purwokerto, 2021)
The study aimed to determine the effect of fruit addition, the percentage of addition, and the interaction between the two treatments on variable pH, total acid, and yogurt viscosity produced. The research material is fresh cow's milk from BBPTU Baturraden, conventional yogurt from online stores, red dragon fruit, ambon bananas, and strawberries from traditional markets. This study used a Completely Randomized Block Design (CRBD) factorial, repeated three times. The first factor is the type of fruit (red dragon, ambon banana and strawberry), the second factor is the percentage of juice addition (K1 = 0%, K2 = 2%, K3 = 4% and K4 = 6%(v/v)). The study results concluded that the type of fruit did not affect the pH, total acid, and viscosity of the produced yogurt. In contrast, the percentage of addition of cider affected the total acid and viscosity of yogurt. The higher the percentage of addition of juice, the lower the total acid and viscosity. The interaction of fruit type treatment and the percentage of addition of juice affects the viscosity of yogurt. The lowest viscosity of yogurt produced in strawberry types with an increase of 6% produces a viscosity of 271.60 mPa.s.